Techno-economic performance optimization of hydrothermal doublet systems: Application to the Al Wajh basin, Western Saudi Arabia. (November 2022) - Ezekiel, Justin; Ebigbo, Anozie; Arifianto, Indra; Daniilidis, Alexandros; Finkbeiner, Thomas; Mai, P. Martin
Highlights: Techno-economic performance optimization of hydrothermal doublet systems is conducted. Well spacing is optimized using a combination of performance metrics. LCOH range of 29 to 76 $/MWh derived for the hydrothermal doublet systems in Al Wajh. LCOH for Al Wajh hydrothermal systems are comparable to those reported elsewhere. LCOH is influenced by reservoir transmissivity, drilling costs and injection temperature. Abstract: The Kingdom of Saudi Arabia (KSA) has vast geothermal energy resources. When developed, these markedly strengthen the country's goals of achieving a carbon-neutral economy. To demonstrate the feasibility and techno-economic performance of small-scale, hydrothermal well doublet systems for direct use in KSA, we perform reservoir and wellbore flow and heat-transport simulations as well as an economic analysis. The maximum permissible flowrate is constrained to avoid thermoelastic fracturing in the near-wellbore region. Reservoir conditions of a sedimentary basin along the Red Sea coast (near Al Wajh) provide an ideal study case to which we add economic parameters considered representative for KSA. We derive a Levelized Cost of Heat (LCOH) ranging from 49 to 128 $/MWh for 50-mD hydrothermal doublet systems with an optimal well spacing of 600 m and a flowrate ranging from 110 kg/s to 50 kg/s. LCOH is strongly influenced by decreasing reservoir transmissivity. Also, a minimum injection temperature is required to avoid thermoelastic fracturing. Our economic analysis further highlights that capacity factor and well-drilling cost have the greatest impact on LCOH. Thus, this study provides a guide and workflow to conduct techno-economic investigations for decision-making, risk mitigation, optimizing geothermal-energy-extraction and economic-performance conditions of hydrothermal doublet systems.